A Transnational Urban Political Ecology of Water Infrastructures: Global Water Policies and Water Management in Hanoi. (April 2019) - Wright-Contreras, Lucía
Using the lens of a transnational urban political ecology of water infrastructures in Vietnam, this article contributes to the understanding of the intersections between urbanization patterns, socioecological problems, financial schemes, and the power relations embedded in Hanoi's urban water supply through politics of scale that aim to ensure safe drinking water. With the analysis of global water policies and their implications in the Southeast-Asian context, the objectives of this work are to (a) reveal the scalar nature of Hanoi's water infrastructures by situating water management processes in a broader context of developmental issues, and (b) review lessons and prospects of past and future global targets of access to safe drinking water. The evidence of multilevel water governance processes and cross-sectoral challenges of safe water provision emphasizes the need for global networks of cooperation to achieve the Sustainable Development Goal 6 and contribute to other sectors aiming to "transform our world."